PARTICIPATORY WEB GIS MANAGEMENT IN TOURISM AREA - Sekarsih, Fitria Nuraini; Kusnawi, Kusnawi; Mustopa, Ali (Universitas Negeri Malang, 2024)
One of the most influential media in conveying information is online media. Through this media, the wider community can get information quickly without being constrained by distance. An interesting area that is increasingly popular because of the role of online media is the Nglanggeran Ancient Volcano Nglanggeran A.V) Tourism Area. However, reviewing information from photos and videos is certainly not enough. For tourists, spatial (location)-based information is fundamental. With this spatial-based information, potential visitors can find interesting points in this tourism area. It is necessary to introduce a tourism-based geographic information system (WebGIS) for this area. Pokdarwis (Tourism Awareness Group) of Nglanggeran Village, which young people dominate, was expected to be able to develop a tourism-based information system. Pokdarwis members had been introduced to WebGIS nglanggeran.gis.co.id, which was initiated before. Then, the Pokdarwis members were introduced and managed this WebGIS. The conclusion of these activities are 1). WebGIs are absolutely needed for the smart tourism village, 2). the need for easy-to-understand management of WebGIS, in managing this WebGIS, 3). the need for assistance periodically to keep updating important information in the Nglanggeran A.V area.